REFRAMING KEGAGALAN AKADEMIK MAHASISWA MELALUI LENSA POST-TRAUMATIC GROWTH: TINJAUAN KONSEPTUAL - Erry Indriani; Susan Rahmayani (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Academic failure in higher education, including delayed graduation, failed thesis defense, unplanned leave, and dropout, is often interpreted as an indicator of individual or institutional deficits. Although research on post-traumatic growth (PTG) has expanded within the contexts of clinical trauma and severe life events, understanding of how academic failure as a nonphysical adversity may influence students’ meaning-making processes and psychological development remains limited. This article aims to develop a theoretical proposition explaining the potential mechanisms linking academic failure, self-schema disruption, cognitive processes, and the possibility of psychological growth from a PTG perspective. This study employed a narrative literature review of research on academic burnout, emerging adulthood, shame in collectivistic contexts, meaning-making, rumination, and PTG. The literature was identified through Google Scholar, PubMed, and PsycINFO and analyzed thematically to integrate relevant concepts into an explanatory framework. A total of 19 key sources were analyzed because they provided direct theoretical or empirical foundations for the components of the proposed conceptual model. The literature synthesis indicates that academic failure may disrupt students’ core assumptions, particularly during emerging adulthood, when academic achievement is closely associated with identity formation and future expectations. Psychological change is suggested to be influenced by a shift from intrusive rumination toward deliberate rumination, with social support, reflective mentoring, and a supportive campus climate serving as facilitating factors. Conversely, shame, stigma, and punitive evaluations may maintain distress by reinforcing avoidance and negative cognitive processing. This article proposes a conceptual framework in which academic failure triggers self-schema disruption that may lead either to prolonged distress or to the five domains of PTG through rumination mechanisms. The proposition requires empirical validation before being used as a basis for interventions or institutional policies. This review provides a foundation for developing more reflective academic mentoring and student counseling services that are responsive to experiences of academic failure. ABSTRAK Kegagalan akademik di perguruan tinggi, seperti keterlambatan kelulusan, kegagalan sidang, cuti tidak terencana, dan putus studi, sering dipahami sebagai indikator defisit individu atau institusi. Meskipun kajian mengenai post-traumatic growth (PTG) telah berkembang dalam konteks trauma klinis dan peristiwa hidup berat, pemahaman mengenai bagaimana kegagalan akademik sebagai adversitas nonfisik dapat memengaruhi proses pemaknaan dan perkembangan psikologis mahasiswa masih terbatas. Artikel ini bertujuan mengembangkan proposisi teoretis yang menjelaskan mekanisme potensial antara kegagalan akademik, gangguan skema diri, proses kognitif, dan kemungkinan munculnya pertumbuhan psikologis melalui perspektif PTG. Kajian ini menggunakan tinjauan literatur naratif terhadap penelitian mengenai burnout akademik, emerging adulthood, shame dalam konteks kolektivistik, meaning-making, rumination, dan PTG. Literatur ditelusuri melalui Google Scholar, PubMed, dan PsycINFO, kemudian dianalisis secara tematik untuk mengintegrasikan konsep-konsep yang relevan ke dalam kerangka penjelasan. Sebanyak 19 sumber utama dianalisis karena memberikan dasar langsung bagi komponen-komponen model konseptual yang dikembangkan. Sintesis literatur menunjukkan bahwa kegagalan akademik berpotensi menjadi pengalaman yang mengguncang asumsi diri, terutama pada masa emerging adulthood ketika pencapaian akademik berkaitan dengan identitas dan masa depan. Proses perubahan psikologis diperkirakan dipengaruhi oleh pergeseran dari intrusive rumination menuju deliberate rumination, dengan dukungan sosial, pendampingan reflektif, dan iklim kampus yang suportif sebagai faktor yang dapat memfasilitasi proses tersebut. Sebaliknya, shame, stigma, dan evaluasi yang menghukum dapat mempertahankan distres melalui penguatan penghindaran dan pemrosesan pikiran negatif. Artikel ini menghasilkan suatu proposisi konseptual yang menempatkan kegagalan akademik sebagai pemicu gangguan skema diri yang dapat berkembang menuju distres berkepanjangan atau lima domain PTG melalui mekanisme rumination. Proposisi ini masih memerlukan pengujian empiris sebelum digunakan sebagai dasar intervensi atau kebijakan. Kajian ini memberikan landasan bagi pengembangan pendampingan akademik yang lebih reflektif dan layanan konseling mahasiswa yang responsif terhadap pengalaman kegagalan.